Role of gonadally synthesized steroid hormones in the colorectal cancer microenvironment - Wenxuan, Liu; Liu, Li; Zhang, Lilong; Qiu, Zhendong; Wu, Zhongkai; Deng, Wenhong (Frontiers in Oncology, 2023)
To understand the relationship between steroid hormones synthesized by the gonads and colorectal cancer as well as its tumor microenvironment, in the expectation of providing new ideas in order to detect and treat colorectal cancer.Methods: Through reviewing the relevant literature at home and abroad, we summarized that androgens promote the growth of colorectal cancer, and estrogens and progesterone help prevent bowel cancer from developing.; these three hormones also have a relevant role in the cellular and other non-cellular components of the tumor microenvironment of colorectal cancer.The current literature suggests that androgens, estrogens, and progesterone are valuable in diagnosing and treating colorectal cancer, and that androgens promote the growth of colorectal cancer whereas estrogens and progesterone inhibit colorectal cancer, and that, in addition, the receptors associated with them are implicated in the modulation of a variety of cellular components of the microenvironment of colorectal cancer.